Ordinary Jack - Cresswell, Helen (Cresswell, Helen. Bagthorpe saga, 1977)
Eleven-year-old Jack, the only "ordinary" member of the talented and eccentric Bagthorpe family, concocts a scheme to distinguish himself as a modern-day prophet.